Sugar or salt ("SOS"): A protocol for a UK multicentre randomised trial of mannitol and hypertonic saline in severe traumatic brain injury and intracranial hypertension. (May 2022) - Rowland, MJ; Veenith, T; Scomparin, C; Wilson, MH; Hutchinson, PJ; Kolias, AG; Lall, R; Regan, S; Mason, J; Andrews, PJD; Horner, D; Naisbitt, J; et al.
Hyperosmolar solutions are widely used to treat raised intracranial pressure following severe traumatic brain injury. Although mannitol has historically been the most frequently administered, hypertonic saline solutions are increasingly being used. However, definitive evidence regarding their comparative effectiveness is lacking. The Sugar or Salt Trial is a UK randomised, allocation concealed open label multicentre pragmatic trial designed to determine the clinical and cost-effectiveness of hypertonic saline compared with mannitol in the management of patients with severe traumatic brain injury. Patients requiring intensive care unit admission and intracranial pressure monitoring post-traumatic brain injury will be allocated at random to receive equi-osmolar boluses of either mannitol or hypertonic saline following failure of routine first-line measures to control intracranial pressure. The primary outcome for the study will be the Extended Glasgow Outcome Scale assessed at six months after randomisation. Results will inform current clinical practice in the routine use of hyperosmolar therapy as well as assess the impact of potential side effects. Pre-planned longer term clinical and cost effectiveness analyses will further inform the use of these treatments.